2012
DOI: 10.1099/mic.0.052134-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide phylogenetic analysis of differences in thermotolerance among closely related Acetobacter pasteurianus strains

Abstract: Acetobacter pasteurianus is a Gram-negative strictly aerobic bacterium that is widely used for the industrial production of vinegar. Three Acetobacter pasteurianus strains, SKU1108, NBRC 3283 and IFO 3191, have the same 16S rRNA sequence (100 % sequence identity) but show differences in thermotolerance. To clarify the relationships between phylogeny and thermotolerance of these strains, genome-wide analysis of these three strains was performed. Concatenated phylogenetic analysis of a dataset of 1864 orthologue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In addition, ABC transporter proteins and transporter-related proteins were identified in this study (spot nos. 38, 157, 173, 194), which are involved in transport systems and might be responsible for the AcOH tolerance and thermotolerance [10,14].…”
Section: Bioinformatic Analysis Of Identified Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, ABC transporter proteins and transporter-related proteins were identified in this study (spot nos. 38, 157, 173, 194), which are involved in transport systems and might be responsible for the AcOH tolerance and thermotolerance [10,14].…”
Section: Bioinformatic Analysis Of Identified Proteinsmentioning
confidence: 99%
“…Previous studies suggested that OMPs (OmpA, OmpW) might be related to the resistance to AcOH and thermotolerance [1,10]. Heat shock proteins (HSPs) are crucial in the inherent folding of proteins under normal growth conditions and can protect the proteins from aggregation and denaturation caused by heat or other environmental stresses [1,10,12]. In this study, HSPs and HSPs-related protein, including DnaK (Hsp70), HtpG (Hsp90), GroEL (Hsp60), HspA (Hsp20/alpha), Clp protease ATP-binding subunit ClpB, ATP-dependent Clp protease proteolytic subunit, and endopeptidase DegP (spot nos.…”
Section: Bioinformatic Analysis Of Identified Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…As its important application value, the whole-genome of A. pasteurianus has been sequenced completely [9,10]. This research is focused on the repair excinuclease UvrA from A. pasteurianus AC2005.…”
Section: Introductionmentioning
confidence: 99%